Another New Horizon? Music technology for senior adults. Issue 3 (7th December 2012) - Stringham, David A.; Ackerman, Paul R.
Music ensembles for senior adults provide participants with musical and social benefits. For various reasons - from disinterest to infirmity to depression and withdrawal - such programmes engage a relatively small segment of a growing and changing senior adult population. Discussions between a university faculty member and a retired psychologist and music therapist led to a question: if senior adults learned to engage with music using technology, would those experiences offer opportunities for musical growth, personal expression and social interaction like those available in music ensembles? In this article, we describe our process for developing a music technology course for senior adults, including a review of literature and findings from a regional survey of senior adults. We also identify considerations for planning, outline a prospective course of study, and provide recommendations for future research and educational efforts related to senior adults and music technology.